2019
DOI: 10.5194/isprs-archives-xlii-3-w6-211-2019
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Condition Index: A Potential Yield Estimator

Abstract: <p><strong>Abstract.</strong> Early yield assessment at local, regional and national scales is a major requirement for various users such as agriculture planners, policy makers, crop insurance companies and researchers. Current study explored a remote sensing-based approach of predicting the yield of Wheat, Kharif Rice and Rabi Rice at district level, using Vegetation Condition Index (VCI), under the FASAL programme. In order to make the estimates 14-years’ historical database (2003&amp;n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…VCI is an NDVI-derived based index that basically isolates the short-term ecological signals from the longer ones [35,36,42]. In this present study, 18 years (2000-2018) of NDVI were derived from the VCI of a particular region.…”
Section: Computation Of Vegetation Indicesmentioning
confidence: 99%
See 2 more Smart Citations
“…VCI is an NDVI-derived based index that basically isolates the short-term ecological signals from the longer ones [35,36,42]. In this present study, 18 years (2000-2018) of NDVI were derived from the VCI of a particular region.…”
Section: Computation Of Vegetation Indicesmentioning
confidence: 99%
“…Vol.66: e23220781, 2023 www.scielo.br/babt precipitation evapotranspirtation index (SPEI) in the North China region and outcomes revealed that the water conditions in June-July had a good estimation for August or for three months interval data [17]. Dubey S and coauthors (2019) highlighted the role of the VCI index as a potential estimator for wheat and rice yield prediction over the various districts of the States [18].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation